P PELATIHAN PENYUSUNAN MODUL AJAR PADA KONSEP KIMIA BERBASIS CONCEPTUAL CHANGE MODEL BAGI GURU-GURU MGMP KIMIA KABUPATEN DAN KOTA MOJOKERTO: PKM Pendidikan Kimia dengan tim MGMP Kabupaten dan Kota Mojokerto - Eka Permatasari, Rosalina; utiya azizah; mitarlis; findiyani ernawati asih (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Community service (PKM) with the title of training in compiling teaching modules on chemical concepts based on conceptual change models for MGMP chemistry teachers in Mojokerto Regency and City as a form of activity aimed at providing an understanding of conceptual change models as an effort to reduce misconceptions that occur in students. This PKM involves a team of resource persons from the S1 chemistry education study program, FMIPA, Surabaya State University with training participants from the MGMP Chemistry team in Mojokerto Regency and City. The methods of this activity are: 1) conveying the conceptual change model using lecture, discussion, question and answer, and workshop methods, 2) assignment method (continued workshop) to be completed within a period of one month (2-4 weeks), and 3) discussing or reflecting on the implementation of PKM. The materials presented consist of: 1) Merdeka Curriculum and its learning tools, 2) core material of conceptual change modules to remediate misconceptions in chemical concepts. Mentoring and progress checking activities were carried out online synchronously via zoom meeting on August 31, 2024. The results of this training can improve the competence of teachers participating in the PKM training with success indicators in the form of conceptual change module products for chemical concepts that were successfully collected until the end of September 2024. Some of these modules include the material on colligative properties of solutions, reaction rates, covalent bonds, chemical bonds, acids, bases and fatty acids. Based on the final product, it can be concluded that training activities can improve the competence of teachers even though the participation value is still low at 46.15% of participants who compiled the conceptual change module. This activity also received a positive response with 84.60% of participants stating that the conceptual change model training was very useful from all training participants. Keywords: misconception, conceptual change model, chemistry